(untitled) - Matejová, Miriam (Aura musica, 2021)
This study deals with the choral and sacred compositions of Mária Jašurdová, a renowned composer active in Slovakia. Her choral compositions Kyrie, Salve Regina, and Ave Maria are performed frequently. Just as her opuses are well-known in Slovakia, we believe they will gradually gain a foothold abroad, too.
Keywords: Mária Jašurdová; sacred; choral compositions